Application value of metagenomic next-generation sequencing in hematological patients with high-risk febrile neutropenia - Wang, Xiao; Zhang, Huiye; Zhang, Nan; Zhang, Shan; Shuai, Yanrong; Miao, Xiaojuan; Liu, Yilan; Qiu, Ling; Ren, Shihui; Lai, Sihan; Han, Ying; Yao, Hao; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Metagenomic next-generation sequencing (mNGS) is a novel non-invasive and comprehensive technique for etiological diagnosis of infectious diseases. However, its practical significance has been seldom reported in the context of hematological patients with high-risk febrile neutropenia, a unique patient group characterized by neutropenia and compromised immune responses.Methods: This retrospective study evaluated the results of plasma cfDNA sequencing in 164 hematological patients with high-risk febrile neutropenia. We assessed the diagnostic efficacy and clinical impact of mNGS, comparing it with conventional microbiological tests.Results: mNGS identified 68 different pathogens in 111 patients, whereas conventional methods detected only 17 pathogen types in 36 patients. mNGS exhibited a significantly higher positive detection rate than conventional methods (67.7 % vs. 22.0 %, P < 0.001). This improvement was consistent across bacterial (30.5 % vs. 9.1 %), fungal (19.5 % vs. 4.3 %), and viral (37.2 % vs. 9.1 %) infections (P < 0.001 for all comparisons). The anti-infective treatment strategies were adjusted for 51.2 % (84/164) of the patients based on the mNGS results.Conclusions: mNGS of plasma cfDNA offers substantial promise for the early detection of pathogens and the timely optimization of anti-infective therapies in hematological patients with highrisk febrile neutropenia.